EFEKTIVITAS PEMBELAJARAN DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN PAI DI SDN 27 LADANG HUTAN - Ersa Mayoli; M. Isnando Tamrin; Nelfanita (CV. ADIBA AISHA AMIRA, 2024)
The background to writing this article was that students' behavior and interests during the learning process were still low and they tended not to pay attention to the explanation of the material presented by the teacher. Therefore, the researcher raised the title about audio-visual media. Audio visual media is learning media which is a combination of audio (sound) and visuals (images). Audio-visual media displays audio (sound) and visual (image) elements simultaneously so that students will be more interested in learning. The aim of this research is to measure the effectiveness of learning using audio-visual media in PAI subjects. This research uses a qualitative approach with a library research method, namely collecting explanations from various sciences which become guidelines and information for research. Researchers collected articles using Google Scholar. The results of this research show that learning using audio-visual media can improve the learning behavior and interest of students in elementary schools. By using audio-visual media, learning will be more interesting and feel different before and after using the media. The atmosphere in the learning process will be more enjoyable and students will participate while learning is taking place. In this way, learning activities will take place with quality so that effectiveness in learning will be formed and achieved.